1981
DOI: 10.3758/bf03196954
|View full text |Cite
|
Sign up to set email alerts
|

Processing of written and spoken words: Evidence for common coding

Abstract: Common processing systems involved during reading and listening were investigated. Semantic, phonological, and physical systems were examined using an experimental procedure that involved simultaneous presentation of two words: one visual and one auditory. Subjects were instructed to attend to only one modality and to make responses on the basis of words presented in that modality. Influence of unattended words on semantic and phonological decisions indicated that these processing systems are common to the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Investigators have been concerneZd with determining conditions under which facilitation or inhibition occur. Hanson (14) found facilitation when words in the visual and auditory modalities were semantically related and/or redundant; however, in her study attention was directed to one modality at a time.…”
mentioning
confidence: 86%
“…Investigators have been concerneZd with determining conditions under which facilitation or inhibition occur. Hanson (14) found facilitation when words in the visual and auditory modalities were semantically related and/or redundant; however, in her study attention was directed to one modality at a time.…”
mentioning
confidence: 86%
“…This "redundant signals" effect has been particularly evident in studies with a focus on signal detection sensitivity and/or accuracy. Some of these studies have found superior detection performance in a dual-modality presentation as compared to either single modality presentation (2,6,(9)(10).…”
mentioning
confidence: 99%
“…Studies which have compared single and dual-modality presentation conditions on sonar-like tasks have yielded mixed findings (1,(10)(11)(12)(13), although most investigators have concluded that a combined visual and auditory approach should be retained in sonar operation. Recently, Lewandowski and Kobus (14) found that detection threshold was lowered by more than 1.2dB to both visual and auditory targets when they were presented simultaneously rather than separately.…”
mentioning
confidence: 99%
“…For hearing persons, knowledge of written and spoken words are interrelated: Reading involves relating written words to spoken words (Baddeley, 1979;Hanson, 1981;Liberman, Liberman, Mattingly, & Shankweiler, 1980), and there is evidence that phoneme analysis of spoken words is influenced by access to the written representation of the words (Ehri & Wilce, 1980;Morais, Cary, Alegria, & Bertelson, 1979;Seidenberg & Tanenhaus, 1979). The underlying regularities governing orthographic structure are thought to be abstracted through this experience in relating the written and spoken systems (Ehri, 1980;Gibson, Shurcliff, & Yonas, 1970;Liberman et al, 1980).…”
mentioning
confidence: 99%